Multi-antenna GNSS tight combination attitude determination in the urban environment. (1st June 2022) - Zhao, Wenhao; Liu, Genyou; Gao, Ming; Hu, Shengjun
Abstract: It is a challenging task to determine dynamic vehicle attitude using a single-frequency single-epoch multi-antenna global navigation satellite system (GNSS). In the urban environment, the number of visible satellites drops sharply due to the occlusion of trees and tall buildings, hence it is difficult to obtain the high-precision attitude of vehicles using only a multi-antenna GNSS. The GNSS tight combination algorithm selects the same reference satellite between different systems, and can effectively increase the number of observation equations after eliminating the inter-system bias, to improve the attitude accuracy of vehicles in complex environments. Compared with the loose combination algorithm, which selects reference satellites separately between different systems, the tight combination algorithm can further improve the locatable performance when there are fewer satellites. Dynamic vehicle experiments were carried out in an open environment and a complex environment, respectively, using the GPS/BDS/GALILEO three-system single-frequency and single-epoch positioning mode. The results show that the tight combination algorithm and the loose combination algorithm have the same accuracy when there are enough visible satellites in the open environment. In a complex environment, with a cut-off elevation angle of 40°, the percentage of pitch angle error, yaw angle error and roll angle error within 2° increased by 6.1%, 8.07% and 13.43%, respectively, and the ambiguity fixed rate was increased by 14.78%.